The Continuing Trouble with Collaboration: Teachers Talk - Lawrence Leonard; Pauline Leonard (Arizona State University, 2015)
The institutionalization of collaborative working environments is widely considered to be critical to the creation and maintenance of schools as professional learning communities. Prevailing thought suggests that improved student performance may be fully realized only when teachers routinely function as teams and abandon their traditional norms of isolationism and individualism. This interpretive study involving teachers in 45 North Louisiana schools suggests that while some schools and school districts are indeed characterized by elements of the `learning community' others remain largely mired in customary practices that are counterproductive to realizing the newer collaborative standards. Participating teachers report that, despite the rhetoric, major impediments to joint professional work remain and they make suggestions for better meeting the continuing collaborative challenge.